Molecular alterations in patients with benign thyroid goitre and papillary thyroid cancer: Genomic and proteomic investigations / Mardiaty Iryani Abdullah - Mardiaty Iryani, Abdullah (2018)
Benign thyroid tumours account for most nodular thyroid diseases. However, determination of whether a thyroid nodule is benign or malignant is a clinical dilemma. Hence, molecular diagnosis may contribute to an improved assessment of thyroid nodules for the distinction of benign and malignant tumours. In the present study, molecular alterations in patients with benign thyroid goitre (BTG) and papillary thyroid cancer (PTC) were profiled using genomic and proteomic approaches. In the genomics study, nucleotide alterations in thyroid tissues were screened using whole-exome sequencing (WES) in patients with BTG (n = 4) and PTC (n = 5). WES led to the discovery of 340 variants in 36 thyroid neoplasm-related genes. Filtering of variants against public databases revealed 23 novel nucleotide alterations, including 12 in the intronic regions, 6 non-synonymous and 4 synonymous changes, and 1 frame-shift deletion. In silico functional analyses indicated that the following novel mutations; c.5908T>C and c.4604A>G of TG, c.1082G>T of TPO, c.353G>A of TRH, and c.262A>C of RASSF1 affected normal activity of the encoded proteins. Further transcript investigation of thyroid tissue of a PTC patient with a frame-shift deletion, termed c.19-50_53CTGdel, verified for the presence of a novel LGALS3-IFI27 chimeric mRNA. Molecular analysis using multiple OMIC techniques was followed up on one of the patients who had concurrent benign and malignant thyroid tissues. WES of her PTC tissue identified c.1799T>A and c.353G>A mutations in the BRAF and TRH genes, respectively. However, only the TRH c.353G>A mutation was detected when PCR direct sequencing was performed on the benign cyst of the patient. Both the malignant and benign tissues had high BRAF expression with decrease or loss of expression of multiple iodide iv metabolism genes. Analyses by 2-dimensional electrophoresis and Ingenuity Pathway analysis indicated “reactive oxygen species insult”, “tissue injury/inflammation”, “cell proliferation” and “apoptosis and necrosis inhibitions” in the benign cyst. Both the tissues demonstrated different expression patterns of activated signal transducer and activator of transcription 3 (pY-STAT3) in western blot experiments, with the benign tissue expressing a novel putative 28 kDa STAT3 isoform, termed STAT3ε. In the subsequent proteomics study, a gel-based approach was performed to analyse the expression of proteins in tissue and serum samples of PTC patients without (PTCa; n = 8) and with a history of BTG (PTCb; n = 6), relative to patients with BTG (n = 20). While higher levels of alpha-1 antitrypsin (A1AT) and heat shock 70 kDa protein were associated with PTCa, lower levels of A1AT, protein disulfide isomerase, and ubiquitin-conjugating enzyme E2N seemed apparent in PTCb. In case of the serum proteins, higher abundances of A1AT and alpha 1-beta glycoprotein were detected in PTCa, while PTCb was associated with enhanced apolipoprotein A4 and alpha 2-HS glycoprotein (AHSG). The different altered expression of tissue and serum A1AT as well as serum AHSG between PTCa and PTCb patients were validated by ELISA. The distinctive altered abundances of the tissue and serum proteins form preliminary indications that PTCa and PTCb may be two distinct cancers of the thyroid that are etiologically and mechanistically different.